Ultrazvok ščitnice - Jarc, Anže (Medicinski razgledi, 2024)
An ultrasonography (US) of the thyroid gland is an accessible and non-invasive method that provides valuable information for characterizing thyroid diseases. It enables the measurement of dimensions and the calculation of thyroid gland and thyroid nodule volume, as well as the assessment of echogenicity, structure, vascularization, and elasticity of the tissue. A healthy thyroid gland typically exhibits an isoechoic and homogeneous structure. Thyroid nodules are a common pathology and a US aids in assessing their potential suspiciousness. Compared to benign nodules, malignant ones often exhibit a solid and hypoechoic structure, a higher width-to-height ratio on transverse projection, irregular edges, microcalcifications, and have a higher elasticity index. A scintigraphy of the gland is also essential for the diagnostic characterization of the nodule, as a US-guided fine-needle biopsy is specifically recommended for scintigraphically cold nodules but not for hyperfunctional (autonomous) nodules. By using a thyroid US, we cannot reliably distinguish between different thyroid diseases that affect the entire thyroid gland, the most common of which are Hashimoto’s thyroiditis, Graves’ disease, postpartum thyroiditis, and subacute thyroiditis. Valuable information for defining the listed diseases can be obtained by assessing the vascularization of the thyroid tissue, which is more pronounced in Graves’ disease, with elastography as a promising additional diagnostic option. Defining thyroid disease and deciding on further treatment is often challenging, as many individuals concurrently have two or even more thyroid diseases, a reliable assessment can thus only be based on a comprehensive thyroidological approach, which includes history, clinical examination, laboratory diagnostics, thyroid US, and in selected cases, thyroid scintigraphy, and US-guided fine needle biopsy.
Keywords: doplerski UZ; elastografija; ščitnica; ščitnični modus; tiroiditis; UZ